2001
DOI: 10.1161/hy1001.095774
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Blood Pressure, Arterial Stiffness and Wave Reflections With a Very-Low-Dose Perindopril/Indapamide Combination in Hypertensive Patient

Abstract: Abstract-International guidelines recommend that antihypertensive drug therapy should normalize not only diastolic (DBP) but also systolic blood pressure (SBP). Therapeutic trials based on cardiovascular mortality have recently shown that SBP reduction requires normalization of both large artery stiffness and wave reflections. The aim of the present study was to compare the antihypertensive effects of the very-low-dose combination indapamide (0.625 mg) and perindopril (2 mg) (Per/Ind) with the ␤-blocking agent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
287
5
27

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 418 publications
(335 citation statements)
references
References 33 publications
16
287
5
27
Order By: Relevance
“…It is potential that the beneficial effects on vascular homoestasis can occur with or without a fall in cuff BP of the brachial artery and may explain the pressure-independent effects of some drugs, such as angiotensin converting enzyme inhibitor (ACEI), angiotensin receptor blocker (ARB) and calcium channel blocker (CCB). [2][3][4][5]36 Therefore, optimal treatment of high BP should include evaluation of arterial elasticity, augmentation index of aortic pressure and left ventricular wasted energy, all of which should be reduced to the lowest level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is potential that the beneficial effects on vascular homoestasis can occur with or without a fall in cuff BP of the brachial artery and may explain the pressure-independent effects of some drugs, such as angiotensin converting enzyme inhibitor (ACEI), angiotensin receptor blocker (ARB) and calcium channel blocker (CCB). [2][3][4][5]36 Therefore, optimal treatment of high BP should include evaluation of arterial elasticity, augmentation index of aortic pressure and left ventricular wasted energy, all of which should be reduced to the lowest level.…”
Section: Discussionmentioning
confidence: 99%
“…1 Although antihypertensive pharmacotherapy with the specific and arbitrary goal to modify BP profiles significantly reduced vascular events, emerging evidence indicates that with equivalent effects on lowering blood pressure, some but not all antihypertensive agents, lead to more reduction of vascular events. 2,3 This apparently beneficial effects beyond BP lowering may be, at least in part, because of further improvement of agent-related vascular properties, [2][3][4][5][6] suggesting that the evaluation of vascular function may be useful complement to brachial BP levels, and may provide more sensitive and specific markers for the vascular risk stratification.…”
Section: Introductionmentioning
confidence: 99%
“…AIx is fairly easily measured by applanation tonometry and therefore less time consuming than measuring PWV; 2 in addition, AIx may be modifiable to a higher degree than PWV. 3,4 However, concerns have been raised as to whether AIx is a reliable measurement of vascular compliance in the elderly 5,6 due to the curvilinear association between AIx and age. 6,7 Interestingly, findings have been contradictory regarding AIx as predictor of CVD where AIx has been associated with increased risk of CVD in highrisk populations 8,9 and in men, 10,11 while its use as a predictor in women 12,13 and in the general population is less certain.…”
Section: Introductionmentioning
confidence: 99%
“…The very low-dose combination perindopril 2 mg (ACE inhibitor)/Indapamide 0.625 mg (diuretic) combination (Per/Ind) Per 2/Ind 0.625 mg has shown a superior antihypertensive efficacy in comparative study vs atenolol, losartan and irbesartan [19][20][21][22][23] and studies in elderly patients and patients with renal impairments. 24,25 In long-term studies (1 year), Per/Ind combination has demonstrated a sustained efficacy with a high normalisation rate and a superiority to atenolol on systolic mean and pulse pressure.…”
Section: Journal Of Human Hypertensionmentioning
confidence: 99%
“…24,25 In long-term studies (1 year), Per/Ind combination has demonstrated a sustained efficacy with a high normalisation rate and a superiority to atenolol on systolic mean and pulse pressure. 19,26,27 In different pharmacological models of LVH, Per/Ind combination has shown its capacity to reverse left ventricular mass. [28][29][30][31] A preliminary double-blind controlled study comparing the lowdose combination Per/Ind and atenolol has shown the higher capacity of Per/Ind to decrease the LVM in hypertensive patients.…”
Section: Journal Of Human Hypertensionmentioning
confidence: 99%